Smart Nanosensitizers for Activatable Sono‐Photodynamic Immunotherapy of Tumors by Redox‐Controlled Disassembly. (31st January 2023) - Liu, Lingjun; Zhang, Junya; An, Ruibing; Xue, Qi; Cheng, Xi; Hu, Yuxuan; Huang, Zheng; Wu, Luyan; Zeng, Wenhui; Miao, Yinxing; Li, Jie; Zhou, Yu; et al.
Abstract: Tumor‐targeted and stimuli‐activatable nanosensitizers are highly desirable for cancer theranostics. However, designing smart nanosensitizers with multiple imaging signals and synergistic therapeutic activities switched on is challenging. Herein, we report tumor‐targeted and redox‐activatable nanosensitizers (1‐NPs ) for sono‐photodynamic immunotherapy of tumors by molecular co‐assembly and redox‐controlled disassembly. 1‐NPs show a high longitudinal relaxivity ( r 1 =18.7±0.3 mM −1  s −1 ), but "off" dual fluorescence (FL) emission (at 547 and 672 nm), "off" sono‐photodynamic therapy and indoleamine 2, 3‐dioxygenase 1 (IDO1) inhibition activities. Upon reduction by glutathione (GSH), 1‐NPs rapidly disassemble and remotely release small molecules 2‐Gd, Zn‐PPA‐SH and NLG919, concurrently switching on (1) dual FL emission, (2) sono‐photodynamic therapy and (3) IDO1 inhibition activities. After systemic injection, 1‐NPs are effective for bimodal FL and magnetic resonance (MR) imaging‐guided sono‐photodynamic immunotherapy of orthotropic breast and brain tumors in mice under combined ultrasound (US) and 671‐nm laser irradiation. Abstract : Tumor‐targeted and glutathione (GSH)‐activatable nanosensitizers (1‐NPs ) are fabricated via co‐assembly and disassembly processes, which confer burst release of small molecules 2‐Gd, Zn‐PPA‐SH and NLG919 within tumor cells, enabling fluorescence and magnetic resonance bimodal imaging‐guided sono‐photodynamic immunotherapy of orthotopic 4T1 breast tumors and deep‐seated GL261 gliomas in mice upon irradiation with combined ultrasound (US) and 671‐nm laser (hv).